2016
DOI: 10.14569/ijacsa.2016.070435
|View full text |Cite
|
Sign up to set email alerts
|

Content-Based Image Retrieval for Medical Applications with Flip-Invariant Consideration Using Low-Level Image Descriptors

Abstract: Abstract-Content-Based Image Retrieval (CBIR) has recently become one of the most attractive things in medical image research. Most existing research on CBIR focused on lowlevel image descriptors in image retrieval, which sometimes weaken the retrieval accuracy since many relevant images are not retrieved. Limited number of researches consider flipping the image on different sides. In order to fill the knowledge gap, this research focuses on considering the flipped images in retrieval based on previously imple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…Various features and their method of representations are described. Qusai Q. Abuein et al, [20] focused their research and concluded about the performance of the current and old systems used for retrieving the flipped images. Ricardoda Silva Torres et al, [21] proposed content based information retrieval approach and proved the existence of automatic retrieval process.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Various features and their method of representations are described. Qusai Q. Abuein et al, [20] focused their research and concluded about the performance of the current and old systems used for retrieving the flipped images. Ricardoda Silva Torres et al, [21] proposed content based information retrieval approach and proved the existence of automatic retrieval process.…”
Section: Literature Reviewmentioning
confidence: 99%